Gorillas are right-handed for their most frequent intraspecific gestures. (August 2016) - Prieur, Jacques; Pika, Simone; Barbu, Stéphanie; Blois-Heulin, Catherine
Abstract : Investigations of intraspecific laterality of primates' gestural communication aim to shed light on the evolutionary origins of human handedness and language. Currently, little is known concerning laterality of gestures for purely intraspecific communication. As far as we know, this study is the first to assess laterality of gorillas' purely intraspecific gestures at the population level. We analysed hand use in dyadic interactions in 35 gorillas, Gorilla gorilla gorilla, living in three groups in captivity focusing on their most frequent communication gesture types. We revealed a right-hand bias at the population level for the majority of the most frequent gestures recorded. Our findings support the evolutionary theories predicting that population level asymmetry should be found in fitness-relevant social behaviours and could be explained by an evolutionarily stable strategy based on intraspecific interactions. They also agree with reports evidencing predominant right-hand use for gestural communication by nonhuman primates and suggesting that gestural laterality is a precursor of the left-hemispheric lateralization of language. Highlights: Gorillas are right handed for the most frequent intraspecific gestures considered. Laterality bias at the population level evidenced for intraspecific interactions. Gestural laterality would be a precursor of the language left-brain specialization.